Investigating the Effect of Cognitive–Behavioral, Mindful-Based, Emotional-Based Intervention and Professional Training on Teachers’ Job Burnout: A Meta-Analysis - Jian Li; Eryong Xue; Yunshu He (Behavioral Sciences, 2023)
Teachers are more likely to experience occupational burnout; intervention for their job burnout has been paid more and more attention by the academic community. However, there is not enough evidence to support the interventions’ effect. This study adopts the meta-analysis method and makes a statistical analysis of the interventions’ effect on teachers’ job burnout based on 29 papers in the literature of randomized controlled experiments. It mainly presents the basic external characteristics of the research literature; besides, based on the results of software CMA.V3, this paper also analysed the overall intervention effect and the separate effect of four types of intervention, namely, cognitive–behavioral interventions (CBI), mindfulness-based interventions (MBI), professional training (PT), and emotional-based intervention (EBI). The results showed that CBI had the best effect, and mindfulness-based intervention had the second-best effect. Professional training also showed a good intervention effect, while the intervention effect of emotional-based intervention remains to be verified. In addition, it was found that only the effect of cognitive–behavioral intervention (CBI) was significant and had a strong effect (g = 0.876, 95% CI-1.06, 2.814, p < 0.05) when considering their effects on emotional exhaustion, while the other three interventions had no significant effect. The discussion section is provided last.